1995
DOI: 10.1002/elps.11501601322
|View full text |Cite
|
Sign up to set email alerts
|

Lung tumor cells: A multivariate approach to cell classification using two‐dimensional protein pattern

Abstract: High resolution two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) is a powerful research tool for the analytical separation of cellular proteins. The qualitative and quantitative pattern of polypeptides synthesized by a cell represents its phenotype and thus defines characteristics such as the morphology and the biological behavior of the cell. By analyzing and comparing the protein patterns of different cells it is possible to recognize the cell type and also to identify the most typical features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Quantitative serum protein proteomics was used to show that a panel of high abundance acute phase-related proteins could give a better statistical measure of inflammation than the classical marker serum amyloid A (41). Cancer tissue samples could be analyzed to distinguish tumor type and prognosis (146), and a panel of six cancer markers in plasma was found to be useful (147,148). More recently, mass spectrometry-based proteomic approaches have been used as well to discover patterns of diseaserelated protein features related to a specific cancer (65).…”
Section: Plasma Diagnosticsmentioning
confidence: 99%
“…Quantitative serum protein proteomics was used to show that a panel of high abundance acute phase-related proteins could give a better statistical measure of inflammation than the classical marker serum amyloid A (41). Cancer tissue samples could be analyzed to distinguish tumor type and prognosis (146), and a panel of six cancer markers in plasma was found to be useful (147,148). More recently, mass spectrometry-based proteomic approaches have been used as well to discover patterns of diseaserelated protein features related to a specific cancer (65).…”
Section: Plasma Diagnosticsmentioning
confidence: 99%
“…Specific protein differences between different types of cancer have been identified by other groups. In a recent study of breast, ovary and lung tumors, 20 differentially expressed proteins were identified [9] and in a prior study, 16 polypeptides were found to be associated with different histopathological features of lung cancer [10,11]. In a study of 25 adenocarcinomas of the lung, 12 small cell lung cancers, and 16 squamous cell tumors, by our group (manuscript submitted) an initial analysis of protein 2-D patterns uncovered a group of 52 protein spots that differed in average integrated intensity between the three groups.…”
Section: Unique Proteomic Pattern Of Small Cell Lung Cancermentioning
confidence: 99%
“…Two-dimensional (2-D) gels offer the potential of defining developmental stages by their global pattern of gene expression. The possibility of using statistical methods to classify 2-D gel profiles has been used by Anderson et al [l] and Schmid et al [2] for comparative studies of different cell cultures. The first description of multivariate methods for the detection of progressive changes in a series of 2-D gel electrophoretic patterns was reported by our laboratories in a study of the heat shock response in a procaryotic bacteria, Streptomyces coelicolor [3].…”
Section: Introductionmentioning
confidence: 99%